Dynamic baselines for the detection of water quality impacts – the case of shale gas development. Issue 8 (30th June 2021) - Worrall, Fred; Davies, Richard J.; Hart, Alwyn
Abstract : Shale gas, geothermal resources and CO2 storage require secure water storage at depth in the Earth. This study shows that the specific conductance of groundwater can be used to detect deep waters leaking from depth. Abstract : There is a need for the development of effective baselines against which the water quality impacts of new developments can be assessed. The specific conductance of flowback water from shale gas operations is typically many times the specific conductance of surface water and near-surface groundwater. This contrast in specific conductance means that specific conductance could be the ideal determinand for detecting water quality impacts from shale gas extraction. If specific conductance is to be used for detecting the impacts of shale gas operations, then a baseline of specific conductance in water bodies is required. Here, Bayesian hierarchical modelling of specific conductance was applied across English groundwater. The modelling used existing, spot-sampled data from the years 2000 to 2018 from 537 unique borehole locations. When the differences between boreholes was considered, then the approach was sufficiently sensitive to detect 1% mixing of fracking fluid in groundwater at a 95% confidence interval. The Bayesian hierarchical modelling maximises the return on public investment and provides a means by which future observations can be judged.